2020
DOI: 10.1177/1534734620912102
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol–Based Nanocerium Improves Healing Responses in Excisional and Incisional Wound Models in Rats

Abstract: Applications of nanotechnology have gained progressive interest for regeneration of injured wound tissue. The aim of the present study was to evaluate effects of polyethylene glycol (PEG)-based nanocerium on excisional and incisional wound models in rats. For excisional wound healing model, 24 male white Wistar rats were randomized into 4 groups of 6 rats each: control group with creation of wounds and no treatment, PEG group with creation of wounds and dressing the wound with PEG, NanoCer group with applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…INFCTD-HMLT-CNM animals showed significantly higher new vessel formation in comparison with INFCTD-CNM and INFCTD-HAMLET groups. Enhanced new vessel formation after wound creation indicated that cinnamon nanoparticles as well as HAMLET could promote the healing process due to enhancement in cellular infiltration [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…INFCTD-HMLT-CNM animals showed significantly higher new vessel formation in comparison with INFCTD-CNM and INFCTD-HAMLET groups. Enhanced new vessel formation after wound creation indicated that cinnamon nanoparticles as well as HAMLET could promote the healing process due to enhancement in cellular infiltration [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We followed the methods of others for biochemical investigations [ 16 , 17 ]. To do this, we took the specimens of wound tissue and assessed their enzyme activities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In rats, Kardan et al 15 have demonstrated that polyethylene glycol-based nanocerium facilitates healing in excisional and incisional wounds. Again in rats, Javanmardi et al 16 have examined the effect of Gundelia tournefortii L extract and milk cream on burns.…”
mentioning
confidence: 99%